Ten lectures on quantitative approaches in cognitive linguistics : corpus-linguistic, experimental, and statistical applications - Gries, Stefan Thomas, 1970- (Distinguished lectures in cognitive linguistics., 2017)
This series of lectures provides an overview of the author's work on quantitative applications in cognitive linguistics by discussing a wide range of studies involving corpus-linguistic as well as experimental work. After a discussion of how corpus linguistics, cognitive linguistics, and psycholinguistics relate to each other, the author discusses empirical and statistical studies of a wide variety of phenomena including morphophonology (morphological blends and alliteration effects), corpus-based cognitive semantics, frequency and association at the syntax-lexis interface. The book concludes with chapters exemplifying the role that bottom-up approaches can take, the role of statistical methods more generally, and the role of converging evidence from corpus and experimental data. The lectures for this book were given at the 'The China International Forum on Cognitive Linguistics' in May 2013.